2004
DOI: 10.1158/1078-0432.ccr-04-1402
|View full text |Cite
|
Sign up to set email alerts
|

Approval Summary

Abstract: Purpose: Docetaxel, a taxane previously approved for the treatment of breast cancer and non-small cell lung cancer, was approved by the United States Food and Drug Administration on May 19, 2004 for use in combination with prednisone for the treatment of metastatic androgen-independent (hormone-refractory) prostate cancer. The purpose of this summary is to review the database supporting this approval.Experimental Design: In a randomized, global study enrolling 1,006 patients, two schedules of docetaxel were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 13 publications
3
55
0
Order By: Relevance
“…Based on these results, thrice-weekly docetaxel with prednisone therapy was approved by the FDA for the treatment of metastatic CRPC in May 2004 and is now widely accepted as the standard of care for chemotherapy in patients with CRPC (14)(15)(16). A recent update of the TAX 327 study, stemmed from an extended follow-up, is consistent with previously reported results.…”
Section: Systemic Chemotherapysupporting
confidence: 78%
See 2 more Smart Citations
“…Based on these results, thrice-weekly docetaxel with prednisone therapy was approved by the FDA for the treatment of metastatic CRPC in May 2004 and is now widely accepted as the standard of care for chemotherapy in patients with CRPC (14)(15)(16). A recent update of the TAX 327 study, stemmed from an extended follow-up, is consistent with previously reported results.…”
Section: Systemic Chemotherapysupporting
confidence: 78%
“…Mitoxantrone, in combination with prednisone, was shown to play a role in the treatment of patients with CRPC (12,(14)(15)(16). A Canadian phase III study in patients with symptomatic CRPC demonstrated that, compared to prednisone alone, this combination resulted in a significant improvement in both response rate (29% versus 12%: p=0.01) and duration of palliation (43 versus 18 weeks: p<0.0001) (12).…”
Section: Systemic Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…It received full FDA approval in 2004 based on a 2.4-month improvement in median overall survival (OS) for docetaxel compared with mitoxantrone [HR ¼ 0.76; 95% confidence interval (CI), 0.62-0.94; P < 0.009; ref. 1,2]. Since then, docetaxel has been commonly used for patients with mCRPC, particularly for those with symptomatic or visceral disease.…”
Section: Introductionmentioning
confidence: 99%
“…The use of high response rates in nonrandomized trials has proved to be a very reliable basis for approving anticancer agents (13). On the other hand, randomized survival comparisons (particularly in unselected patients) can be very misleading (14), and have led to the approval of a wide range of agents that yield statistically significant results but provide limited benefits for unselected patients (Table 1) (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Such survival-based randomized studies in unselected patients may miss a marked benefit in defined subpopulations, or alternatively it may result in a drug being widely applied even though it benefits only a small minority of patients (27).…”
Section: -5 ó2010 Aacrmentioning
confidence: 99%